Indios, ciudadanía y tributo en la independencia neogranadina. Antioquia (1810-1816) (2014)
ABSTRACT: This article examines the Superior Declaration in favor of freedom of the tributary Indians of the Province of Antioquia (1811) and the strategic and creative responses of some indian villages immediately and in the following years. This situation led to debates about indigenous citizenship in the region, in the context of First Republic in New Granada. Economic disadvantages and dissolution of protection indigenous institutions were some of the reasons why there was a major trend, although not unanimous, of these communities to preserve their statu quo.